An examination of managers' perceptions of turnover and retention in the hotel industry: Are hotel managers doing enough to address the issue of turnover? - McClean, Colin (Auckland University of Technology, 2006)
Hotel employees leave their jobs at an alarming rate. Amongst those that leave are individuals who possess the talent and ability to become the hotel leaders of the future. With alarming levels of employee turnover, it is important to question what action managers in the industry are taking to curb the trend. An examination of the employee turnover literature showed that the hotel industry is suffering from high levels of turnover. Whilst the literature offers a comprehensive account of the existence of high employee turnover in the hotel industry, little is known of the measures hotel managers are taking to counter this issue. Hotel managers hold great responsibility in addressing employee turnover as their policies and practices have an important impact on employee turnover. Therefore, a problem exists in a lack of understanding of managers’ perceptions of employee turnover and their efforts to address high employee turnover. Without an understanding of management practices and perceptions, we are unable to accurately predict the future state of employee turnover in the hotel industry. Two steps were taken in this research to address a lack of understanding relating to hotel managers’ views of employee turnover. A comprehensive literature review was undertaken, and hotel managers who shared an average of 10.5 years experience in the hotel industry completed a total of 15 questionnaires. The questionnaires were analysed to draw out the perceptions of managers and to offer insight as to how hotel managers are countering high levels of employee turnover. The questionnaires were analysed in relation to the findings of the literature review. From that analysis a number of observations were made that offer insight into the perceptions and performance of managers in the hotel industry. The following key points emerged from the research. Firstly, the participants indicated that issues related to pay are the primary cause of employee turnover. Secondly, the survey results suggested that while the participants are aware of the importance of pay in employee decisions to leave a hotel, they chose to focus their retention efforts on issues such as training, career advancement, and fostering open communication. Thirdly, despite expressing concern at the level of turnover in the hotel industry, the participants were divided on whether or not anything can be done to prevent it. Fourthly, the policies they supported, such as career tracking and career development, can be seen to encourage turnover rather than decrease it.
Keywords: Hotels -- Personnel management